Educational processes of training, retraining and advanced training of private detectives in Ukraine - Kyslyi, A.; Pysmenna, M.; Kolomoiets, O.; Volobuieva, O.; Bezusyi, V. V.; Безусий, В. В.; ORCID: http://orcid.org/0000-0001-6452-5672 (Cuestiones Políticas. – 2020. – Vol. 38, Nº Especial (lera parle). – P. 421-435, 2020)
Метою статті було здійснити ретроспективний аналіз нормативно-правових актів щодо легалізації приватної детективної діяльності в Україні та, водночас, розглянути особливості підготовки, перепідготовки та підвищення кваліфікації приватних детективів з метою подальшого вдосконалення законодавства у цій сфері.

The aim of the article was to carry out a retrospective analysis of the legal acts on the legalization of private detective activities in Ukraine and, at the same time, consider the characteristics of training, retraining and advanced training of private detectives in order to to further improve legislation in this area. The subject of the study is essentially the process of training, retraining and advanced training of private detectives in Ukraine. During the research, the following scientific methods were used: dialectical method, methods of synthesis and analysis, methods of induction and deduction, statistical method, historical and legal and formal and legal methods. The peculiarities of the Law of Ukraine “On the Activity of Private Detective (Search)” were considered, its advantages and disadvantages were described. By way of conclusion, he emphasizes that the existing legal education system, introduced in civil educational institutions, is not adequate for the training of private detectives. For these and other political and legal reasons, the need to train private detectives in the system of higher education institutions with specific learning conditions in the heat of the requirements imposed by reality itself is argued.

Целью статьи было провести ретроспективный анализ законодательных актов о легализации частной детективной деятельности в Украине и вместе с тем рассмотреть особенности подготовки, переподготовки и повышения квалификации частных детективов с целью дальнейшего совершенствовать законодательство в этой сфере.

El objetivo del artículo fue realizar un análisis retrospectivo de los actos jurídicos sobre la legalización de las actividades de detective privado en Ucrania y, al mismo tiempo, considerar las características de la formación, el reciclaje y la formación avanzada de los detectives privados con el fin de mejorar aún más la legislación en esta área. El tema del estudio es esencialmente el proceso de formación, reciclaje y formación avanzada de detectives privados en Ucrania. En el curso de la investigación se utilizaron los siguientes métodos científicos: método dialéctico, métodos de síntesis y análisis, métodos de inducción y deducción, método estadístico, métodos históricos y legales y formales y legales. Se consideraron las peculiaridades de la Ley de Ucrania «Sobre la actividad de detective privado (búsqueda)», se describieron sus ventajas y desventajas. A modo de conclusión desataca que el sistema de educación jurídica existente, introducido en las instituciones educativas civiles, no es adecuado para la formación de detectives privados. Por estas y otras razones políticas y jurídicas, se argumenta la necesidad de formar detectives privados en el sistema de instituciones de educación superior con condiciones específicas de aprendizaje al calor de los requerimientos que impone la propia realidad.
Procesos educativos de formación, reciclaje y formación avanzada de detectives privados en Ucrania
Educational processes of training, retraining and advanced training of private detectives in Ukraine / Kyslyi Anatolii, Pysmenna Mariia, Kolomoiets Oleksandr, Volobuieva Olena, Bezusyi Vadym // Cuestiones Políticas. – 2020. – Vol. 38, Nº Especial (lera parle). – P. 421-435.
Keywords: publikatsii u WoS; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; private detective; private detective agencies; vocational training; recycling; advanced training; приватний детектив; частный детектив; частные детективные агентства; приватні детективні агентства; професійне навчання; профессиональное обучение; навчання; training